Evaluate the expression. Assume that all the angles are in Quadrant I. (cos (arctan √3/7))

Evaluate the expression. Assume that all the angles are in Quadrant I. (cos (arctan √3/7))

Related Posts

This Post Has 4 Comments

  1. 0.971

    Step-by-step explanation:

    Given the expression (cos (arctan √3/7)) which all lies in the first quadrant. Note that all the trigonometry identities (sin, cos and tan) are all positive in the first quadrant.

    From the expression given

    (cos (arctan √3/7)), we need to get the expression in parenthesis first.

    Let y = (cos (arctan √3/7))

    If u = arctan √3/7

    Then y = cos(u) 1

    Let's get the value of u first

    u = arctan √3/7

    u = arctan(0.2474)

    u = 13.896°

    Substituting u = 13.896° into equation 1, we will have;

    y = cos(u)

    y = cos13.896°

    y = 0.971.

    Hence the expression (cos(arctan√3/7)) is equivalent to 0.971

  2. y = 0.971.

    Step-by-step explanation:

    Given the expression (cos (arctan √3/7)) which all lies in the first quadrant. Note that all the trigonometry identities (sin, cos and tan) are all positive in the first quadrant.

    From the expression given

    (cos (arctan √3/7)), we need to get the expression in parenthesis first.

    Let y = (cos (arctan √3/7))

    If u = arctan √3/7

    Then y = cos(u) 1

    Let's get the value of u first

    u = arctan √3/7

    u = arctan(0.2474)

    u = 13.896°

    Substituting u = 13.896° into equation 1, we will have;

    y = cos(u)

    y = cos13.896°

    y = 0.971.

Leave a Reply

Your email address will not be published. Required fields are marked *